Erratum: One-month spaceflight compromises the bone microstructure, tissue-level mechanical properties, osteocyte survival and lacunae volume in mature mice skeletons. Issue 1 (December 2017) - Gerbaix, Maude; Gnyubkin, Vasily; Farlay, Delphine; Olivier, Cécile; Ammann, Patrick; Courbon, Guillaume; Laroche, Norbert; Genthial, Rachel; Follet, Hélène; Peyrin, Françoise; Shenkman, Boris; Gauquelin-Koch, Guillemette; et al.
A correction to this article has been published and is linked from the HTML version of this paper. The error has been fixed in the paper.